Mary Ann Watters correspondence - Watters, Mary Ann.
ALS (1862 November 5) from Watters of Des Moines, Iowa, to Adjutant General Nathaniel B. Baker concerning the enlistment of her husband, James Watters, in the 39th Iowa Volunteer Infantry Regiment.
Wife of Union Army soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Baker, Nathaniel B. -- 1818-1876 -- Correspondence; Watters, James, -- f. 1862.; United States. -- Army -- Recruiting, enlistment, etc. -- Civil War, 1861-1865.; United States. -- Army. -- Iowa Infantry Regiment, 39th (1862-1865); Iowa -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.